2007
DOI: 10.7861/clinmedicine.7-4-351
|View full text |Cite
|
Sign up to set email alerts
|

New medical options for liver tumours

Abstract: -Significant progress is being made in the prevention of hepatitis B-related hepatocellular carcinoma (HCC) but hepatitis C-related HCC is increasing in the West and therapeutic advances in established disease have been modest. Although ablative therapies, including surgical resection, seem effective in patients with small tumours these only represent a minority of patients. For the majority with advanced disease there is some evidence for survival benefit for transarterial chemoembolisation but only in very c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The management of HCC that is considered too extensive for surgical resection or RFA, poses a difficult and unresolved dilemma in the role of therapeutic choices to assist in palliative care1,2,19,20 In recent years, a strategy of choice is the direct delivery of chemotherapy via the hepatic artery directly to the tumor vasculature2,14,15,20 The present clinical experience was obtained in 2 sequential cohorts of patients with unresectable, advanced HCC. In the first group, we describe our overall experience of patients treated with a structured protocol of cisplatin infusion, accompanied by gelfoam or Embospheres arterial embolization, which was designed to reduce but not completely obstruct (embolize)14 the hepatic arterial blood flow and to minimize side effects (TACE group).…”
Section: Discussionmentioning
confidence: 99%
“…The management of HCC that is considered too extensive for surgical resection or RFA, poses a difficult and unresolved dilemma in the role of therapeutic choices to assist in palliative care1,2,19,20 In recent years, a strategy of choice is the direct delivery of chemotherapy via the hepatic artery directly to the tumor vasculature2,14,15,20 The present clinical experience was obtained in 2 sequential cohorts of patients with unresectable, advanced HCC. In the first group, we describe our overall experience of patients treated with a structured protocol of cisplatin infusion, accompanied by gelfoam or Embospheres arterial embolization, which was designed to reduce but not completely obstruct (embolize)14 the hepatic arterial blood flow and to minimize side effects (TACE group).…”
Section: Discussionmentioning
confidence: 99%
“…Reynaert and Colle, summarized WHO 2018 statistics analysis and reported that liver cancer is the sixth frequent type of cancer with the 4th leading cause of cancer-related death worldwide and also indicated an increasing trend of incidence and death rat [ 389 ]. Many other primary cancers metastasize into the liver, the most notable being the colorectal cancer [ 390 ]. At the early stage of tumour surgical eradication of the tumour is the treatment of choice in 30% of the HCC cases.…”
Section: Somatostatin and Liver Cancermentioning
confidence: 99%
“…There is some evidence for survival benefit, but only in very carefully selected patients. [ 44 ] The systemic therapy using chemotherapy, immunotherapy, hormonal therapy or somatostatin analog have been disappointing in patients with advanced HCC. [ 45 ] Since HCC is a hypervascular cancer, gene therapy may be used for anti-angiogenesis to reduce tumor growth, and is a promising approach to treat HCC.…”
Section: Relation Between Hepatitis C and Hepatocellular Carcinomamentioning
confidence: 99%